FENOMENA WISATAWAN MANCANEGARA DENGAN MASALAH KESEHATAN MENTAL DALAM PANDANGAN STAKEHOLDER PARIWISATA BALI - I Putu Sagita Jaya Utama; I Made Arsa Wiguna (PARIWISATA BUDAYA: JURNAL ILMIAH PARIWISATA AGAMA DAN BUDAYA, 2023)
Traveling activities could not be separated from all forms of tourist activities either both benefits and consequences faced by tourist destinations. The presence of tourists, especially foreign tourists with mental health problems, is a real phenomenon that occurs in Bali. This situation certainly deserves to be studied to see what factors play a role and become the cause and stakeholder views on this phenomenon. With the method of observation and in-depth interviews with informants consisting of mental health experts, community leaders, tourism facility managers and intellectual figures who were selected purposively and supported by several printed and digital sources of information as triangulation material. So the results of the study indicate that there are genetic and organic aspects that play an important role in causing the phenomenon of mental health disorders for foreign tourists visiting Bali, in terms of internal factors. Then there are changes in the physical environment, socio-economic conditions as well as the emergence of cultural shocks from the external side. Then a hypothesis emerges which is expected to open up space for stakeholders to think, that there is a reality of foreign tourists with mental health problems behind the euphoria of Bali's tourism success.